Morphological characterization of Leucaena leucocephala and Leucaena diversifolia hybrids - de Freitas, Liane Helena Cardoso; Paim, Nilton Rodrigues; Schifino-Wittmann, Maria Teresa (Pesquisa Agropecuaria Brasileira, 1995)
L. leucocephala is the most world-wide known species of the nitrogen-fixing multipurpose trees of the American genus Leucaena Benth. The great genetic variability allows crosses and selection aiming at specific needs as cold and acid-soils tolerance. In the present work an hybrid population of L. leucocephala (Lam) de With. (2n=104) x L. diversifolia (Schlecht) Benth (2n=104), established at the Estação Experimental Agronômica of the Universidade Federal do Rio Grande do Sul (EEA - UFRGS), at Eldorado do Sul, RS, Brazil, was analyzed regarding leaf length, number of pinnae and leaflet pairs, number, arrangement and colour of flowers in the inflorescences, number of legumes per inflorescence and seeds per legume and 100-seed weight. The hybrid population was rather tolerant to frost and intermediate between parents for leaf length, number of pinnae and leaflet pairs, flower arrangement and number of seeds per legume. L. leucocephala genome predominated for flower number and colour.